In Defence of Reasonable Doubt. Issue 2 (23rd February 2016) - Gardiner, Georgi
Abstract: In criminal trials the state must establish, to a particular standard of proof, the defendant's guilt. The most widely used and important standard of proof for criminal conviction is the 'beyond a reasonable doubt' standard. But what legitimates this standard, rather than an alternative? One view holds the standard of proof should be determined or justified – at least in large part – by its consequences. In this spirit, Laudan uses crime statistics to estimate risks the average citizen runs of being violently victimised and falsely convicted. He argues that since the former risk is higher, and the aggregate harms are worse, the standard of proof should be substantially lowered. He presents a formula for calculating the preferred standard. In this article I outline various ways Laudan's uses of crime statistics are flawed, and explain how he substantially overestimates risks of victimhood and underestimates costs of false convictions. I also explain why his formula is mistaken, and illuminate consequences Laudan neglects. I conclude that, even if consequences determine the appropriate standard of proof, Laudan's arguments fail to show the standard is too high. I conclude by suggesting that the inadequacies of Laudan's reasoning might be good news for consequence‐based justifications of the standard of proof.